PENGARUH RETRIBUSI PELAYANAN PASAR, PAJAK HOTEL DAN RESTORAN PADA PENDAPATAN ASLI DAERAH KABUPATEN GIANYAR - Dwi Temaja, I Dewa Gede Agung; Dharma Suputra, I D.G. (E-Jurnal Akuntansi, 2014)
In the current era of regional autonomy, local governments are expected to recognize the potential and the resources they have in order to be extracted and utilized as sources of finance such as local revenues, especially to meet the financing needs of governments and construction for the welfare of its people. The purpose of this study was to determine the effect of market service charges, hotel and restaurant tax to local revenues Gianyar fiscal year 2008-2012. This research was conducted at the Department of Revenue and Gianyar Regency Gianyar Central Bureau of Statistics, this study used secondary data, so the data collection method used was a non-participant observation method. Engineering analysis using multiple linear regression analysis techniques. Based on the analysis, it is known that the levy of service markets, hotel and restaurant taxes have a significant effect on local revenues Gianyar fiscal year 2008-2012. Variable levy market services, hotel and restaurant tax to contribute as much as 60,1 percent of local revenues while the remaining 39,9 percent is influenced by other variables not included in the research model.
Keywords: Retribusi Pelayanan Pasar; Pajak Hotel dan Restoran; Pendapatan Asli Daerah